AirWorld: uma solução tecnológica para o monitoramento da qualidade do ar em ambientes públicos - Souza, Alex da Silva (Brasil, 2023)
Air quality is not adequate in many environments, and monitoring is important to avoid negative health effects. Current solutions require large investments, in addition to having high costs to keep working and people capable of handling them. In this sense, the objective of this research is to present the development of a technological solution to inform the user about air quality, allowing, among other things, the performance of practical or leisure activities in public spaces. The methodology used in this study consisted of a bibliographical research for theoretical foundation and the conception phase. Then, the construction of the technological solution and the prototyping of the application were carried out. As a result, after its development, it can be seen that it met the needs regarding the monitoring of air quality.